2016
DOI: 10.15377/2409-787x.2016.03.01.2
|View full text |Cite
|
Sign up to set email alerts
|

Value Creation with Multi-Criteria Decision Making in Geosteering Operations

Abstract: Due to escalated drilling costs, the petroleum industry has been attempting to access the largest possible hydrocarbon resources with the lowest achievable costs. Multiple well objectives are set prior to the start of drilling. Then, a geosteering approach is implemented to help operators achieve these objectives.A comprehensive literature survey has been performed on geosteering case histories, including many cases with multiple objectives. We found that the listed objectives are often conflicting and express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The ensemble of realizations is updated following each decision using the Ensemble Kalman Filter (EnKF) algorithm described in [4]. 1 For the update we use measurements produced from a synthetic EM tool which is located at the drill-bit and has look-around capability of +/-4.8 meters. The system performs one update between decision points which uses measurements in three equally distributed locations.…”
Section: Automatic Update Of Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…The ensemble of realizations is updated following each decision using the Ensemble Kalman Filter (EnKF) algorithm described in [4]. 1 For the update we use measurements produced from a synthetic EM tool which is located at the drill-bit and has look-around capability of +/-4.8 meters. The system performs one update between decision points which uses measurements in three equally distributed locations.…”
Section: Automatic Update Of Uncertaintymentioning
confidence: 99%
“…The literature review in [1] showed that there was hardly any prior publication that considered a consistent framework for geosteering decision making with several objectives. The authors prepared an alternative decision-focused approach.…”
Section: Introductionmentioning
confidence: 99%
“…A natural requirement for any DSS is the possibility to take into account multiple objectives. The objectives used in modern geosteering operations include placing the well in a specific position in the reservoir, reducing costs and ensuring safety (Kullawan et al, 2016). For the use in a DSS the objectives need to be converted into objective functions defined on a common scale, e.g.…”
Section: Objectivesmentioning
confidence: 99%